2019
DOI: 10.1002/cam4.2330
|View full text |Cite
|
Sign up to set email alerts
|

Modulated electro‐hyperthermia induced p53 driven apoptosis and cell cycle arrest additively support doxorubicin chemotherapy of colorectal cancer in vitro

Abstract: Objective Modulated electro‐hyperthermia (mEHT), a noninvasive complementary treatment of human chemo‐ and radiotherapy, can generate selective ~42°C heat in cancer due to elevated glycolysis (Warburg‐effect) and electric conductivity in malignant tissues. Here we tested the molecular background of mEHT and its combination with doxorubicin chemotherapy using an in vitro model. Methods C26 mouse colorectal adenocarcinoma cultures were mEHT treated at 42°C for 2 × 60 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 46 publications
12
42
2
Order By: Relevance
“…SzIE, ÁOTK MÁB 26/2013 and the most recent one, no. PE/EA/633-5/2018), using mouse C26 colorectal cancer cell line allografted into BALB/c mice, are found in Vancsik et al, 2018 and 2019 [ 12 , 29 ]. In the studies, 10% neutral-buffered, formalin-fixed tumor tissues embedded in paraffin were cut for 2–3 µm thick serial sections and mounted on silanized adhesion glass slides.…”
Section: Standardized Meht Treatment and Protocolsmentioning
confidence: 99%
See 3 more Smart Citations
“…SzIE, ÁOTK MÁB 26/2013 and the most recent one, no. PE/EA/633-5/2018), using mouse C26 colorectal cancer cell line allografted into BALB/c mice, are found in Vancsik et al, 2018 and 2019 [ 12 , 29 ]. In the studies, 10% neutral-buffered, formalin-fixed tumor tissues embedded in paraffin were cut for 2–3 µm thick serial sections and mounted on silanized adhesion glass slides.…”
Section: Standardized Meht Treatment and Protocolsmentioning
confidence: 99%
“…Either using human or animal malignant tumor cell lines under in vitro or in vivo settings, the dominant pathway of tumor destruction after mEHT was apoptosis mediated programmed cell death as opposed to necrosis, as demonstrated mostly using annexin V–propidium iodide flow cytometry [ 29 , 42 ]. Apoptosis was also confirmed by the widespread detection of its characteristic morphological signs in hematoxylin–eosin-stained sections or cell cultures, including nuclear shrinkage and chromatin condensation (picnosis), cell membrane blebbing, and formation of apoptotic bodies ( Figure 1 d) [ 11 , 12 , 18 , 23 ].…”
Section: Meht-induced Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…(Fig. 1a, b) Numerous studies have shown that hyperthermia enhanced intracellular uptake of doxorubicin in different types of tumor cells [19,20]. In this study, we measured doxorubicin positive cells using ow cytometer.…”
Section: Enhanced Cytotoxicity Of Doxorubicin Following Sub-lethal Hymentioning
confidence: 92%